Private Activity in Infrastructure in East Asia and Pacific Declined for Third Consecutive Year in 2010 - Parulekar, Koustubh (World Bank, Washington, DC, 2012)
In 2010, 36 infrastructure projects with private participation reached financial or contractual closing in seven low and middle-income countries, involving investment commitments of US$10.9 billion. Infrastructure projects implemented in the 1990-2009 period attracted new investment of US$4.3 billion, bringing total investment commitments to infrastructure in the region to US$15.2 billion in 2010. The activity in 2010 represents a 9 percent decline by investment and 45 percent drop by number of projects compared with 2009. Investments in new projects fell by 9 percent and in projects implemented in previous years by 10 percent compared with 2009.